SYSTEME UNIVERSEL POUR L’ADMINISTRATION DES DONNEES (SUAD) / (UNIVERSAL SYSTEM FOR THE ADMINISTRATION OF DATA) (USAD) - Dufresne, M.; Cohen, D.H. (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l’ACSI, 2022)
see pdf